Healthcare inequities experienced by patients with cancer: A qualitative study in Medellín, Colombia (2022)
This study aimed to understand the lived experiences of patients with cancer that facing inequities in oncological care in the city of Medellín. Patients and Methods: A qualitative study was conducted based on the theoretical and methodological elements of the grounded theory, specifically the description and conceptual ordering of Corbin and Strauss. Sixteen patients with cancer, who belonged to low (n=5), middle (n=4) and high (n=7) social classes, were included by theoretical sampling with category saturation. Data were collected using semi-structured interviews and analyzed in a category system based on the three social classes. The patients were aged between 23 and 71 years old, and they were diagnosed with different types of cancer such as breast, cervical, prostate, stomach, leukemia and lymphoma. Patients’ experiences showed that diagnosis, specialized care, treatment and hospital discharge were different based on their social class. Patients’ lived experiences associated with cancer reflect complex social situations, in which social determinants affect the level of citizens’ empowerment and self-management against the risks of get disease and die. Being part of low and middle social classes meant being subjected to a dehumanized, cold, impersonal and discontinuous treatment, in which healthcare was focused on the disease instead of individuals’ preferences and values. In contrast, patients belonging to the high class had the resources necessary to face risks, which ensured access to more humanized and individualized healthcare.